ENERGY ECONOMICAL ASPECTS OF THE HEATING FURNACES WORKING - I. V. Kotov; V. A. Matochkin; A. A. Sotnikov; E. V. Bobrova (Литьë и металлургия, 2005)
It is shown that for realization of the balance ''high effectiveness - low level of discharge'' the complex of actions is required, as increasing of one of the indices of the balance always results in decreasing of the other one.